2007
DOI: 10.1073/pnas.0611110104
|View full text |Cite
|
Sign up to set email alerts
|

Restoring species-specific posttransfer editing activity to a synthetase with a defunct editing domain

Abstract: In contrast, the isolated INS domain displays only weak editing activity and lacks tRNA sequence specificity. These results emphasize the modular nature of synthetase editing active sites and demonstrate how in evolution, a weak editing activity can be converted to a more robust state through fusion to the body of a synthetase. In this manner, a single editing module can be distributed to different synthetases, and simultaneously acquire specificity and enhanced activity.Prolyl-tRNA synthetase ͉ Saccharomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…This finding is consistent with the previously published molecular dynamic simulation that the CP1 domain contributes to the cognate amino acid specificity in tryptophanyl-tRNA synthetase (37). It is also consistent with the editing domains of the class II ProRS, which have been fused or appended to the synthetic core at diverse sites (36,38).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This finding is consistent with the previously published molecular dynamic simulation that the CP1 domain contributes to the cognate amino acid specificity in tryptophanyl-tRNA synthetase (37). It is also consistent with the editing domains of the class II ProRS, which have been fused or appended to the synthetic core at diverse sites (36,38).…”
Section: Discussionsupporting
confidence: 75%
“…This was also found for the class II ProRS editing domain, which is fused to a catalytic core that has a completely different fold (36,38). Surprisingly, in the case of LeuRS, this increase in discrimination was also conferred by the addition of the noncognate CP1…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Such mistranslation may lead to observable cellular and disease pathologies such as cell degeneration and apoptosis in mammalian systems (19) and neurodegeneration and ataxia in mice (20). Moreover, since heritable mutations in human glycyl-tRNA synthetase and tyrosyl-tRNA synthetase genes have been directly associated with the peripheral neuropathy Charcot-Marie-Tooth (21,22), the role of the aaRSs and their editing function in maintaining translational fidelity have become areas of intense study (23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Previous work showed that the N-terminal extension of S. cerevisiae ProRS (ScProRS) has low homology with the INS domain, and it is deprived of some key residues, which may be the relics of a previously functional domain. Although editing-deficient, it still contributes to the catalytic rate of the whole enzyme (39).…”
Section: Cp1 Domain Benefits Hmtleurs In Catalyticmentioning
confidence: 99%